[M2(μ‐OH)2(DHBQ)3] (M = Zr, Hf) ‐ Two New Isostructural Coordination Polymers based on the Unique M2O14 Inorganic Building Unit and 2, 5‐Dioxido‐p‐benzoquinone as Linker Molecule. Issue 5 (9th November 2020) - Poschmann, Mirjam P. M.; Reinsch, Helge; Stock, Norbert
Abstract : Two new isostructural porous coordination polymers (CPs) were obtained under solvothermal reaction conditions using 2, 5‐dihydroxy‐ p ‐benzoquinone (H2 DHBQ) or 1, 2, 4, 5‐tetrahydroxybenzene (H4 THB) as linker molecule and Zr 4+ or Hf 4+ salts. Highly crystalline compounds with composition [M2 (μ‐OH)2 (DHBQ)3 ]· x H2 O (M = Zr 4+ or Hf 4+, x = 0–3.6/3.3) were found in a wide temperature range (120–200 °C) and a reaction time of 70 h. The crystal structures were determined ab initio from powder X‐ray diffraction data and the oxidation state of the linker was confirmed spectroscopically. The dinuclear inorganic building unit M2 O14 is new for Zr‐ and Hf‐CPs. For both compounds a full characterization was carried out, i.e. crystal structure determination, spectroscopic measurements, elemental‐ and thermogravimetric analyses. [M2 (OH)2 (DHBQ)3 ] (M = Zr 4+ or Hf 4+ ) is stable up to 250 and 220 °C, respectively. Water sorption measurements proofed an uptake of 3.6 mol H2 O per mol and 3.3 mol H2 O per mol, respectively. Abstract :